2008
DOI: 10.1051/forest:2008012
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan and mortality of old oaks — combining empirical and modelling approaches to support their management in Southern Sweden

Abstract: To cite this version:Igor Drobyshev, Mats Niklasson, Hans Linderson, Kerstin Sonesson, Matts Karlsson, et al.. Lifespan and mortality of old oaks -combining empirical and modelling approaches to support their management in Southern Sweden. Annals of Forest Science, Springer Verlag/EDP Sciences, 2008, 65 (4), pp.1. Ann. For. Sci. 65 (2008) Abstract -• Old oaks (Quercus robur L.) play an important role in the southern Scandinavian landscape by providing habitat for a wide range of species, a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
4
20
0
1
Order By: Relevance
“…Drobyshev et al species (Grime et al, 1988). For oak, the mortality rate obtained in our study (1.0% annually for condition class 1 and 2 trees) was identical to the average rate of 1% reported for mature oaks growing in a wide range of habitats across Europe (Drobyshev et al, 2008). For small-leaved linden, our estimate (0.8%) was close to the rate reported for this species in a Danish natural old-growth forest (0.5%, Wolf, 2004).…”
Section: Mortality Rate and Its Determinantssupporting
confidence: 73%
See 1 more Smart Citation
“…Drobyshev et al species (Grime et al, 1988). For oak, the mortality rate obtained in our study (1.0% annually for condition class 1 and 2 trees) was identical to the average rate of 1% reported for mature oaks growing in a wide range of habitats across Europe (Drobyshev et al, 2008). For small-leaved linden, our estimate (0.8%) was close to the rate reported for this species in a Danish natural old-growth forest (0.5%, Wolf, 2004).…”
Section: Mortality Rate and Its Determinantssupporting
confidence: 73%
“…These results support the view that competitive interaction might be the dominant mortality factor for small trees in Oranienbaum Park. A review of oak mortality rates in Europe (Drobyshev et al, 2008) suggested that its mortality rate is generally correlated with stand density. Similar results were obtained for Norway spruce (Repola et al, 2006).…”
Section: Interaction Effects On Mortality Ratesmentioning
confidence: 99%
“…The low annual mortality rate in beech may be related to its late successional status and the opposite holds for the pioneer birch. However, the high mortality rate of pedunculate oak, well above birch, is higher than expected for temperate forests (Drobyshev et al, 2008). Specially, since no catastrophic events occurred during the studied period.…”
Section: Discussionmentioning
confidence: 96%
“…In the upper Elbe valley, Lorenz (2013) described a decrease of suitable trees of approximately 3% to 5% per year. This decline is higher than the annual mortality rates given by Drobyshev et al (2008) of about 1% for oak populations located outside dense forests. At a rate of 3%, it would take only 10 to 15 years to lose a quantity of TOW comparable to that which was observed between 1973 and 2009.…”
Section: Conclusion and Implication For The Conservation Of O Eremitamentioning
confidence: 62%